Do clinical tests of spasticity accurately reflect muscle function during walking: A systematic review. (21st March 2017) - Banky, Megan; Ryan, Hannah K.; Clark, Ross; Olver, John; Williams, Gavin
ABSTRACT: Objective : The aim of this systematic review was to establish the ecological validity of clinical tests of lower limb spasticity by determining whether the range of motion (ROM) and speed of limb movement during the assessment accurately replicate muscle function and joint biomechanics during walking. Methods : An electronic search of ten databases was performed to identify all relevant articles. The reference lists of all included articles were also searched. Identification of relevant articles, data extraction and quality assessment were performed independently by two reviewers. Results : Seventeen studies were included in the review. The Modified Ashworth Scale was the most commonly used clinical measure of lower limb spasticity. The ROM and speed of assessment were poorly reported for clinical scales of lower limb spasticity, making it difficult to draw conclusions regarding the relevance of these scales to walking performance. Conclusions : The ecological validity of the clinical scales of spasticity could not be determined as studies did not adequately report their testing procedure. Further research into the ecological validity of clinical scales of spasticity is required in order to better understand the impact that spasticity has on functional activities such as walking.